Aportes de la filosofía "lean construction" a la optimización de procesos en la gestión de proyectos de la empresa Talero Ingeniería (2017)
In this document, we look at the concepts of the construction company Talero Ingeniería as a company Mipyme within the contextual framework for the study of the contributions of the lean construction philosophy to the optimization of processes in the management of projects in order to identify a model of optimization and improvement within the management of the company. It will analyze the historical progress that has had the lean construction philosophy and its antecedents, to then make an analysis of the most optimal lean models for the company development and thus make a study of the current management and a comparison under a vision lean construction in some projects in development by the company.